Surgical Management and Rehabilitation of an Olecranon Fracture in a Patient with Thrombocytopenia-Absent Radii: A Case Report. Issue 2 (April 2021) - Wang, Patrick Qi; Chan, Andrea; Drosdowech, Darren
Abstract : Case: A 29-year-old right-hand dominant woman with thrombocytopenia-absent radii syndrome was surgically treated for a right olecranon fracture. Given her forearm deformity and short lever arm, a custom-modified corrective elbow flexion splint was used during rehabilitation. Radiographic union was achieved. Although functional outcome scores were similar to the ones previously reported in the general population, the patient had persistent extension contracture. Conclusion: Despite good functional outcomes, the patient had reduced range of motion. With severe limb deformity, the greatest challenge is to provide optimal rehabilitation protocols and individualized tools.